2016
DOI: 10.1099/mic.0.000281
|View full text |Cite
|
Sign up to set email alerts
|

PhoB activation in non-limiting phosphate condition by the maintenance of high polyphosphate levels in the stationary phase inhibits biofilm formation in Escherichia coli

Abstract: Polyphosphate (polyP) degradation in Escherichia coli stationary phase triggers biofilm formation via the LuxS quorum sensing system. In media containing excess of phosphate (Pi), high polyP levels are maintained in the stationary phase with the consequent inhibition of biofilm formation. The transcriptional-response regulator PhoB, which is activated under Pi limitation, is involved in the inhibition of biofilm formation in several bacterial species. In the current study, we report, for the first time, we bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 62 publications
(49 reference statements)
2
17
0
Order By: Relevance
“…Collectively, these data demonstrated that PAL5 copper tolerance correlated with the degradation of preformed polyP. In agreement with these results, polyP degradation was identified as a step in an alternative mechanism to detoxify metals in E. coli (13), acidophilic bacteria (1), and archaea (31). Further studies are needed to elucidate other key factors involved in the polyP-dependent metal detoxification system in G. diazotrophicus .…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Collectively, these data demonstrated that PAL5 copper tolerance correlated with the degradation of preformed polyP. In agreement with these results, polyP degradation was identified as a step in an alternative mechanism to detoxify metals in E. coli (13), acidophilic bacteria (1), and archaea (31). Further studies are needed to elucidate other key factors involved in the polyP-dependent metal detoxification system in G. diazotrophicus .…”
supporting
confidence: 81%
“…Polyphosphate (polyP) is a linear polymer of inorganic phosphate (Pi) residues linked by phosphoanhydride bonds and is present in bacteria, archaea, fungi, protozoa, plants, and animals (19). PolyP is involved in physiological and regulatory mechanisms, including motility, competence, biofilm formation, and virulence, in several bacteria and parasites (10, 12, 13, 21, 29). It also plays roles in bacterial survival in the stationary phase and responses to nutrient starvation and other stress conditions (7, 11, 29, 32).…”
mentioning
confidence: 99%
“…PolyP may also influence expression of the Pho regulon during the stationary phase (161). Grillo-Puertas et al showed that during the stationary phase PhoB could be activated when cells were grown in a medium containing high levels of phosphate (∼40 mM P i ) (161). It was demonstrated that this activation depended upon the production of acetyl phosphate and the production of polyP.…”
Section: P I Homeostasismentioning
confidence: 99%
“…PolyP is also involved in cell signaling, respiratory chain gene expression, bacterial persistence, and in stress response networks [93][94][95][96]. It has recently been shown that when external Pi levels are very high, polyP can even activate PhoB during the stati o n a r yp h a s eo fg r o w t ht h r o u g ht h es m a l l molecule acetyl phosphate [97]. It is then postulated that phospho-PhoB inhibits the synthesis of c-di-GMP, blocking the production of AI-2, leading to the inhibition of biofilm formation.…”
Section: The Response To High Levels Of Extracellular Pimentioning
confidence: 99%